Global characteristics of childhood acute promyelocytic leukemia. Issue 2 (March 2015) - Zhang, L.; Samad, A.; Pombo-de-Oliveira, M.S.; Scelo, G.; Smith, M.T.; Feusner, J.; Wiemels, J.L.; Metayer, C.
Abstract Acute promyelocytic leukemia (APL) comprises approximately 5–10% of childhood acute myeloid leukemia (AML) cases in the US. While variation in this percentage among other populations was noted previously, global patterns of childhood APL have not been thoroughly characterized. In this comprehensive review of childhood APL, we examined its geographic pattern and the potential contribution of environmental factors to observed variation. In 142 studies (spanning > 60 countries) identified, variation was apparent—de novo APL represented from 2% (Switzerland) to > 50% (Nicaragua) of childhood AML in different geographic regions. Because a limited number of previous studies addressed specific environmental exposures that potentially underlie childhood APL development, we gathered 28 childhood cases of therapy-related APL, which exemplified associations between prior exposures to chemotherapeutic drugs/radiation and APL diagnosis. Future population-based studies examining childhood APL patterns and the potential association with specific environmental exposures and other risk factors are needed.